Human variant glucose-6-phosphate transporter is active in microsomal transport - Baochuan Lin; Chi-Jiunn Pan; Janice Chou (Human Genetics, 2000)

Copy Number Related Transgene Expression and Mosaic Somatic Expression in Hemizygous and Homozygous Transgenic Tilapia (Oreochromis Niloticus) - M. Azizur Rahman; Gyu-Lin Hwang; Shaharudin Abdul Razak; Frédéric Sohm; Norman Maclean (Transgenic Research, 2000)

Applications of the Mild-Slope Equation to Tidal Computations in the Taiwan Strait - Ming-Chung Lin; Wen-Jye Juang; Ting-Kuei Tsay (Journal of Oceanography, 2000)

Is China learning from its neighbors? A comparison of overseas investment between China and other east Asian economies - Mark Yao-lin Wang (Chinese Geographical Science, 2000)

Antibody responses to respiratory coronavirus infections of cattle during shipping fever pathogenesis - X. Q. Lin; K. L. O’Reilly; J. Storz; C. W. Purdy; R. W. Loan (Archives of Virology, 2000)

Surveys of Volatile Organic Compounds in Soil and Groundwater at Industrial Sites in Taiwan - M.-C. T. Kuo, C.-M. Chen, C. H. Lin, H. C (Bulletin of Environmental Contamination and Toxicology, 2000)

Effects of shear and sharp gradients in static stability on two-dimensional flow over an isolated mountain ridge - Ting-An Wang; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2000)

Characterization and detection of epistatic interactions of 3 QTLs, Hd1, Hd2, and Hd3, controlling heading date in rice using nearly isogenic lines - H. X. Lin; T. Yamamoto; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2000)

Binding of cell type-specific nuclear proteins to the 5′-flanking region of maize C4 phosphoenolpyruvate carboxylase gene confers its differential transcription in mesophyll cells - Mitsutaka Taniguchi; Katsura Izawa; Maurice S.B. Ku; Jenq-Horng Lin; Hideaki Saito; Yuji Ishida; Shozo Ohta; Toshihiko Komari; Makoto Matsuoka; Tatsuo Sugiyama (Plant Molecular Biology, 2000)

Molecular Cloning and Antiserum Development of Cyclin Box in the Brown Tide Alga Aureococcus anophagefferens - Senjie Lin; Erika Magaletti; Edward J. Carpenter (Marine Biotechnology, 2000)

Genome scan identifies a locus affecting gamma-globin level in human beta-cluster YAC transgenic mice - Sluan D. Lin; Phil Cooper; Jingly Fung; Heinz-Ulrich G. Weier; Edward M. Rubin (Mammalian Genome, 2000)

Unusual voltammetry of manganese-substituted myoglobin in surfactant film: evidence for two redox pathways - Rong Lin; Chad E. Immoos; Patrick J. Farmer (JBIC Journal of Biological Inorganic Chemistry, 2000)

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

Sampling efficiency of a modified closed-face cassette sampler for airborne toluene diisocyanate determination - I.-F. Mao; M.-L. Chen; Y.-C. Lin (International Archives of Occupational and Environmental Health, 2000)

Inhibitory effect of esculetin on oxidative damage induced by t -butyl hydroperoxide in rat liver - Wea-Lung Lin; Chau-Jong Wang; Yu-Ying Tsai; Chuen-Lan Liu; Jin-Ming Hwang; Tsui-Hwa Tseng (Archives of Toxicology, 2000)

TGFβ1 stimulates the secretion of matrix metalloproteinase 2 (MMP2) and the invasive behavior in human ovarian cancer cells, which is suppressed by MMP inhibitor BB3103 - Sui-Wen Lin; Ming-Ting Lee; Ferng-Chun Ke; Ping-Ping H. Lee; Chang-Jen Huang; Margot M. Ip; Lily Chen; Jiuan-Jiuan Hwang (Clinical & Experimental Metastasis, 2000)

Temperature anomalies in central and eastern Tibetan Plateau in relation to general circulation patterns during 1951-1993 - Zhi-Yong Yin; Zhenyao Lin; Xinyi Zhao (International Journal of Climatology, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

A simulating study on resolvable—Scale microphysical parameterization in a mesoscale model - Lin Wenshi; Fong Soikun; Wu Chisheng; Ku Chimeng; Wang Anyu; Yang Yan (Advances in Atmospheric Sciences, 2000)

S1 analysis of long PCR heteroduplexes: detection of chloroplast indel polymorphisms in Fragaria - J. Lin; T. M. Davis (Theoretical and Applied Genetics, 2000)

Renal threshold for urinary glucose excretion by tilapia in response to orally administered carbohydrates and injected glucose - Shian-Chuann Lin; Chyng-Hwa Liou; Shi-Yen Shiau (Fish Physiology and Biochemistry, 2000)

The relationship between `deep-hole' mitochondria-rich cells and salinity adaptation in the euryhaline teleost, Oreochromis mossambicus - T.H. Lee; P.P. Hwang; Y.E. Shieh; C.H. Lin (Fish Physiology and Biochemistry, 2000)

Marek's Disease Herpesvirus Transforming Protein MEQ: a c-Jun Analogue with an Alternative Life Style - Juinn-Lin Liu; Hsing-Jien Kung (Virus Genes, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part III: 6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part II: 48-6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part I: 84-48 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)

Plant regeneration from callus culture of a Paphiopedilum hybrid - Yung-Haw Lin; Chen Chang; Wei-Chin Chang (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Differences in the distribution of synemin, paranemin, and plectin in skeletal muscles of wild-type and desmin knock-out mice - Lena Carlsson; Zhen Lin Li; Denise Paulin; Maureen G. Price; Jennifer Breckler; Richard M. Robson; Gerhard Wiche; Lars-Eric Thornell (Histochemistry and Cell Biology, 2000)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)

Species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin; Shiu-Nan Chen (Systematic Parasitology, 2000)

Interstitial colocalization of two cervid satellite DNAs involved in the genesis of the Indian muntjac karyotype - Yueh-Chun Li; Charles Lee; Despina Sanoudou; Tzong-Hsiung Hsu; Shuan-Yow Li; Chyi-Chyang Lin (Chromosome Research, 2000)

Maternal transfer of cadmium tolerance in larval Oreochromis mossambicus - H. C. Lin; S.C Hsu; P.P. Hwang (Journal of Fish Biology, 2000)
Exposing female tilapia to Cd did not affect reproduction and egg quality, nor the survival of their offspring. The LT 50 of Cd‐exposed larvae (within 24 h post hatching) from Cd‐treated female Oreochromis mossambicus (mean ±S.E.=10·9±0·5 days, n =4) was greater than that of Cd‐exposed larvae from control females (6·9± 1·2 days, n =4). A substantial amount of metallothionein mRNA (MT mRNA) was found in both oocytes and newly hatched larvae from Cd‐treated females, but MT mRNA levels were low in newly fertilized eggs. The amount of MT mRNA was very low in all these stages in the control group. Cadmium could not be detected at any stage for either control or Cd‐treated group, and metallothionein protein levels were also very low in both groups. The early appearance of MT mRNA in oocytes and newly hatched larvae from Cd‐treated females may result in early translation after hatching and explain their tolerance to Cd.

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Differential expression of dystrophin, utrophin, and dystrophin-associated proteins in human muscle culture - V. Radojevic; S. Lin; J.-M. Burgunder (Cell and Tissue Research, 2000)

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Photodegradation of the Herbicides Butachlor and Ronstar Using Natural Sunlight and Diethylamine - Y. J. Lin; C. Lin; K. J. Yeh; A. Lee (Bulletin of Environmental Contamination and Toxicology, 2000)

Construction of transformant Alcaligenes latus enforcing its own cloned phbC gene and characterization of poly-β-hydroxybutyrate biosynthesis - Yong-Hyun Lee; Il-Seon Seo; Young-Mi Jung; Tae-Lin Huh (Biotechnology Letters, 2000)

Uncertainty analysis on zonation maps of debris flow hazard in Yunnan Province, China - Xi-lin Liu (Chinese Geographical Science, 2000)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Raman spectroscopic study of hydroxyl-clinohumite at various pressures and temperatures - C.-C. Lin; L.-G. Liu; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2000)

Emissions of N2O, NH3 and NOx from fuel combustion, industrial processes and the agricultural sectors in China - Li Yu'e; Lin Erda (Nutrient Cycling in Agroecosystems, 2000)

Expression of receptor protein tyrosine phosphatase agr; mRNA in human prostate cancer cell lines - Stanislav Zelivianski; Jeanenne Dean; Deepak Madhavan; Fen-Fen Lin; Ming-Fong Lin (Molecular and Cellular Biochemistry, 2000)

Unique chromosome identification and sequence-specific structural analysis with short PNA oligomers - Caifu Chen; Bai-lin Wu; Tao Wei; Michael Egholm; William M. Strauss (Mammalian Genome, 2000)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Headspace ethylene accumulation on Stizolobium hassjoo hairy root culture producing L-3,4-dihydroxyphenylalanine - Lin-Shiang Sung; Shih-Yow Huang (Biotechnology Letters, 2000)

Azo dye decolorization with a mutant Escherichia coli strain - Jo-Shu Chang; Tai-Shin Kuo; Yun-Peng Chao; Jin-Yen Ho; Ping-Jei Lin (Biotechnology Letters, 2000)

Entrainment of Intestinal Slow Waves with Electrical Stimulation Using Intraluminal Electrodes - Xuemei Lin; J. Hayes; L. J. Peters; J. D. Z. Chen (Annals of Biomedical Engineering, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Cloning and expression of the α-amylase gene and oxytetracycline production in Streptomyces rimosus - Chun-Wen Cheng; Jin-Seng Lin; Yu-Tien Liu; Shang-Shyng Yang (World Journal of Microbiology and Biotechnology, 2000)

Somatic embryogenesis and plant regeneration from litchi protoplasts isolated from embryogenic suspensions - Changhe Yu; Zhenguang Chen; Liuxin Lu; Jinwen Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Stability of Human Serum Albumin During Bioprocessing: Denaturation and Aggregation During Processing of Albumin Paste - Jen-Jen Lin; Jeffrey D. Meyer; John F. Carpenter; Mark C. Manning (Pharmaceutical Research, 2000)

Cloning of Two New cry Genes from Bacillus thuringiensis subsp. wuhanensis Strain - White-Shang Kuo; Jong-Huon Lin; Ching-Chou Tzeng; Shui-Shang Kao; Kin-Fu Chak (Current Microbiology, 2000)

Alcohol Consumption and Breast Cancer among Black and White Women in North Carolina (United States) - Anita Yeomans Kinney; Robert C. Millikan; Yu Hua Lin; Patricia G. Moorman; Beth Newman (Cancer Causes & Control, 2000)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)

Rapid early onset lymphocyte cell death in mice resistant, but not susceptible to Leishmania major infection - Julie Desbarats; Jeffrey E. Stone; Lin Lin; Zahra F. Zakeri; Gerald S. Davis; Linda M. Pfeiffer; Richard G. Titus; M. Karen Newell (Apoptosis, 2000)

Differential expression of mouse laminin γ2 and γ2* chain transcripts - Tomi Airenne; Yanfeng Lin; Magnus Olsson; Peter Ekblom; Seppo Vainio; Karl Tryggvason (Cell and Tissue Research, 2000)

A Method of Phase Space Modeling of a Climatological Series and its Application - Zhen-Shan Lin (Meteorology and Atmospheric Physics, 2000)

Release Kinetics of Water Soluble Organic Carbon (WSOC) from River Sediment and Wetland Soil - Shu Tao; Bin Lin; Xiaohang Liu; Jun Cao (Water, Air, & Soil Pollution, 2000)

The Arterial Supply of the Carpal Joint in the Bactrian Camel (Camelus Bactrianus) - Jian-Lin Wang; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

Mitochondrial DNA analysis of Sporothrix schenckii clinical isolates from China - Junping Lin; Masako Kawasaki; Masanori Aoki; Hiroshi Ishizaki; Gang You; Ruoyu Li (Mycopathologia, 2000)

Differential regulation of testosterone vs. 5α-dihydrotestosterone by selective androgen response elements - Pei-Wen Hsiao; Tin Htwe Thin; Din-Lii Lin; Chawnshang Chang (Molecular and Cellular Biochemistry, 2000)

Inhibitory effect of phycocyanin from Spirulina platensis on the growth of human leukemia K562 cells - Yufeng Liu; Lizhi Xu; Ni Cheng; Lijun Lin; Chengwu Zhang (Journal of Applied Phycology, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Arrestment response of the predatory mite Amblyseius longispinosus to Schizotetranychus nanjingensis webnests on bamboo leaves (Acari: Phytoseiidae, Tetranychidae) - Yan-Xuan Zhang; Jie Ji; Zhi-Qiang Zhang; Jian-Zhen Lin (Experimental and Applied Acarology, 2000)

Water Quality and Pollution in the Hunchun Basin, China - Nam-Chil Woo; Ji-Won Moon; Joong-Sum Won; Jeong-Sang Hahn; Xue-Yu Lin; Yong-Sheng Zhao (Environmental Geochemistry and Health, 2000)

The Arterial Supply of the Cubital Joint in the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang; Gao-Lan; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

Serum tocopherols, selenium and lung cancer risk among tin miners in China - Duminda Ratnasinghe; Joseph A. Tangrea; Michele R. Forman; Terry Hartman; Elaine W. Gunter; You-Lin Qiao; Shu-Xiang Yao; Michael J. Barett; Carol A. Giffen; Yener Erozan; Melvyn S. Tockman; Philip R. Taylor (Cancer Causes & Control, 2000)

Characterization of a 5′-flanking region supporting the transcription of mouse thymosin β-4 in mouse NIH3T3 cells - Yeu Su; Shan-Lin Chang; Huang-Liang Hsiao (Molecular and Cellular Biochemistry, 2000)

Artifact reduction in electrogastrogram based on empirical mode decomposition method - H. Liang; Z. Lin; R. W. McCallum (Medical & Biological Engineering & Computing, 2000)

Melanocortin 1 receptor variation in the domestic dog - J.M. Newton; Alison L. Wilkie; Lin He; Siobhán A. Jordan; Danika L. Metallinos; Nigel G. Holmes; Ian J. Jackson; Gregory S. Barsh (Mammalian Genome, 2000)

ESTABLISHMENT AND CHARACTERISTICS OF A HUMAN SIGNET RING CELL GASTRIC CARCINOMA CELL LINE (SJ-89) UNDER SERUM-FREE CONDITIONS - YUCHENG DAI; HUA LIN; LIYA YUAN; JIE LI; YIMIN LI; GUOAN CHEN; JIAN LI (In Vitro Cellular & Developmental Biology - Animal, 2000)